PENERAPAN ALGORITMA SELECTION SORT PADA SISTEM ANTREAN PELANGGAN BERBASIS FIFO UNTUK PENGOLAHAN DATA TRANSAKSI WARUNG TELEPON DI PONDOK PESANTREN SALAFIYAH SAFIIYAH SUKOREJO - Naila Ismi Fadila; Wilda Mukammila; Devi Sucianti; Alfinadiya Alfinadiya (Jurnal Padamu Negeri, 2026)
The rapid development of information technology has encouraged many business sectors to adopt computer-based systems to enhance operational effectiveness. One type of business that still relies on manual record-keeping is the public telephone kiosk (wartel), particularly in managing customer queues and recording transactions. Manual systems often lead to issues such as disorganized queue sequences, errors in transaction data entry, and difficulties in retrieving customer data. This study aims to implement the Selection Sort algorithm in a FIFO-based customer queue system. This implementation is expected to improve the efficiency of transaction data processing at wartel establishments. The FIFO method is applied to manage customer handling based on arrival time, while Selection Sort is used to sort transaction data according to transaction time and payment amount. The system development follows the Waterfall methodology, which consists of requirements analysis, design, implementation, testing, and maintenance. The findings indicate that the combination of FIFO and Selection Sort is effective in helping manage queues and accelerating the process of generating orderly transaction reports. The resulting system improves data accuracy and facilitates staff in delivering better service to customers.